Clinical significance of prognostic nutrition index in hospitalized patients with COVID‐19: Results from single‐center experience with systematic review and meta‐analysis. (16th July 2021) - Rashedi, Sina; Keykhaei, Mohammad; Pazoki, Marzieh; Ashraf, Haleh; Najafi, Atabak; Kafan, Samira; Peirovi, Niloufar; Najmeddin, Farhad; Jazayeri, Seyed Aboozar; Kashani, Mehdi; Moharari, Reza Shariat; Montazeri, Mahnaz
Abstract: Background: We aimed to ascertain risk indicators of in‐hospital mortality and severity as well as to provide a comprehensive systematic review and meta‐analysis to investigate the prognostic significance of the prognostic nutrition index (PNI) as a predictor of adverse outcomes in hospitalized coronavirus disease 2019 (COVID‐19) patients. Methods: In this cross‐sectional study, we studied patients with COVID‐19 who were referred to our hospital from February 16 to November 1, 2020. Patients with either a real‐time reverse‐transcriptase polymerase chain reaction test that was positive for COVID‐19 or high clinical suspicion based on the World Health Organization (WHO) interim guidance were enrolled. A parallel systematic review/meta‐analysis (in PubMed, Embase, and Web of Science) was performed. Results: A total of 504 hospitalized COVID‐19 patients were included in this study, among which 101 (20.04%) patients died during hospitalization, and 372 (73.81%) patients were categorized as severe cases. At a multivariable level, lower PNI, higher lactate dehydrogenase (LDH), and higher D‐dimer levels were independent risk indicators of in‐hospital mortality. Additionally, patients with a history of diabetes, lower PNI, and higher LDH levels had a higher tendency to develop severe disease. The meta‐analysis indicated the PNI as an independent predictor of in‐hospital mortality (odds ratio [OR] = 0.80; P < .001) and disease severity (OR = 0.78; P = .009). Conclusion: Our results emphasized the predictive value of the PNI in the prognosis of patients with COVID‐19, necessitating the implementation of a risk stratification index based on PNI values in hospitalized patients with COVID‐19.